Determination of Sucrose Content in Acacia Honey and X BRAND Honey by Luff-Schoorl Method - Hidayah, Azzahra Zulfa Nur; Sari, Rifqi Nila; Rukmini, Aulia (Journal of Nutraceuticals and Herbal Medicine, 2025)
Honey is a natural liquid that has a sweet taste produced by honey bees from the nectar of flowers (floral nectar), other parts of the plant (extra floral nectar), or insect excretions. Honey is often used as medicine in addition to being used as a sweetener or food flavouring. Acacia honey has a refreshing taste with sour and sweet flavours. The Luff-Schoorl method is a type of chemical-based monosaccharide determination. This experiment aims to determine the sucrose content in Acacia Honey and X BRAND Honey to determine whether the sucrose content is in accordance with the Indonesian National Standard (SNI) 01-3545-2013. Acacia honey has a sucrose content of 0.22% and X BRAND honey 3.46%, so it meets the quality standards. This research showed that the sucrose content is appropriate, namely a maximum of 5%.